Sudden cardiac death in young athletes - Patel, D. R. (Asian Journal of Sports Medicine, 2011)
The article by Halabchi et al. provides a comprehensive, thoughtful and balanced analysis of the literature on sudden cardiac death (SCD) in young athletes. The article is unique in providing a special perspective for Asia as contrasted with those in Europe and the United States. This aspect is extremely important to recognize for the management of young athletes in different parts of the world.